Wetting front dynamic study in Brazilian cements using neutron and X-ray imaging techniques - Higor Rosenberger; Márcio Aparecido Bulla Jr; Estela Oliari Garcez; Nikolay Kardjilov; Fabiano Yokaichiya; Margareth K.K.D. Franco (Next Materials)
Cement-based materials have a complex porous structure that changes over time, and the durability of such materials strongly correlates to the transport of water and ions throughout the pore structure. The type of cement plays an important role on concrete durability. In this study the dynamics of water absorption using three different types of Portland cement: i) high-early strength cement, ii) ground granulated blast furnace slag (GGBFS) blended cement, and iii) pulverized fly ash (PFA) blended cement, at two different curing ages (7 days and 60 days) were investigated. Neutron radiography technique was used for continuous monitoring of the water absorption in cement paste samples, as shown in the film measured by 3 h, showing the radial and longitudinal penetration of water. The evolution of the wetting front was quantified, analyzed and it was observed that the volume of absorbed water presents behavior according to the square root of time based on neutron images for all samples. X-ray tomography technique was used to investigate the differences between the pore structure and volume of pores (air voids). Finally, this article shows that image techniques is a suitable method for analyzing the size, surface and location of single air voids. The combination of the results from X-ray Tomography and Neutron Radiography shows the potential application of these methods for determining air void parameters and demonstrates how microstructure, type of cement and curing time modified the dynamic water absorption. As expect the fastest absorption was observed on the samples cured for 7 days, however results show clear differences between the three types of cement. At the longer curing time, although no significant differences were found in water absorption, there were important differences in the total number and volume of air voids.